2022
DOI: 10.7150/ijbs.73747
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell-derived extracellular vesicles afford neuroprotection by modulating PI3K/AKT pathway and calcium oscillations

Abstract: Mesenchymal stromal cells (MSC) are widely recognized as potential effectors in neuroprotective therapy. The protective properties of MSC were considered to be associated with the secretion of extracellular vesicles (MSC-EV). We explored the effects of MSC-EV in vivo on models of traumatic and hypoxia-ischemia (HI) brain injury. Neuroprotective mechanisms triggered by MSC-EV were also studied in vitro using a primary neuroglial culture. Intranasal administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 98 publications
1
24
0
Order By: Relevance
“…In other experimental groups, the level of C3 and S100a10 gene mRNA expression was higher and had no significant difference from the SCI control group after the transplantation of high doses of MSC-EVs. It was shown that the addition of MSC-EVs to the neuroglia culture can influence/modulate intracellular calcium fluxes in astrocytes but not in neurons [ 23 ]. There are many data showing the participation of calcium ions in hereditary and acquired neuropathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other experimental groups, the level of C3 and S100a10 gene mRNA expression was higher and had no significant difference from the SCI control group after the transplantation of high doses of MSC-EVs. It was shown that the addition of MSC-EVs to the neuroglia culture can influence/modulate intracellular calcium fluxes in astrocytes but not in neurons [ 23 ]. There are many data showing the participation of calcium ions in hereditary and acquired neuropathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MSC-derived EVs have been shown to be able to modulate microglia towards the neuroprotective M2 phenotype and reduce neuroinflammation [ 22 ]. Another study [ 23 ] investigated the Ca 2+ ion-associated intracellular mechanism by examining the neuroprotective effects of MSC-EVs when administered intranasally in two in vivo models of acute brain injury. The authors showed that by activating the PI3K signaling pathway and preventing calcium overload, MSC-EVs protected astrocytes and neurons from cell death under ischemia-like conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the modalities and outcomes of the interaction between the different EV subtypes and the target cells during hypoxic damage are yet to be thoroughly investigated in order to clarify their role and to identify possible new therapeutic approaches. As a matter of fact, EVs contain a wide range of bioactive molecules that can mediate neuroprotection through several mechanisms of action (e.g., antiapoptotic and antioxidative signaling pathways) [ 1 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nervous tissue has a limited regenerative capacity upon several types of damage, both in peripheral nervous tissue and in the central nervous system [ 82 ]. Stem cell-derived EVs have been shown to improve regeneration of the nervous tissue after some types of damage in several animal models, such as peripheral nerve denervation [ 83 , 84 ], trauma [ 85 ], and stroke [ 86 , 87 ], with a neuroprotective effect on models of hypoxic-ischemic encephalopathy [ 69 , 88 ]. These EVs seem to exert this role through different processes and pathways associated with nerve regeneration.…”
Section: Pro-regenerative Effects Of Evsmentioning
confidence: 99%
“…These EVs seem to exert this role through different processes and pathways associated with nerve regeneration. For example, in a recent study, Turovsky et al demonstrated that EVs from MSCs exert a neuroprotective effect in a mouse model of ischemia through the modulation of phosphatidylinositol 3-Kinase/AKT signaling and calcium oscillations [ 69 ]. Moreover, EVs from different sources can induce changes in the glial cells, increasing the percentage of proliferating Schwann cells by 20% and increasing the myelinating potential of oligodendrocytes [ 89 ].…”
Section: Pro-regenerative Effects Of Evsmentioning
confidence: 99%